Incidence of Surgical Complications Following Cesarean Section: A Longitudinal Study - Erum Jahan, Sumera Mahmood, Saiqa Rashid, Saima Shabbir, Rahila Imtiaz, Urvashi Gupta (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the incidence and risk factors of the surgical complications following the caesarian section. Study design: A longitudinal study Place and Duration:This study was conducted at Abbasi Shaheed Hospital, Karachi Medical and Dental College, Karachi from June 2018 to June 2021 Methodology: All the cases of the caesarian section conducted in our hospital in three year were included in this study. In this study, we recruited 79052 cases of caesarian section delivering their first child while 402316 vaginal deliveries were also reported. Short-term complications occurring within 42 days after delivery (puerperium) were also noted. The risk for placenta previa and uterine rupture was also studied. The secondary outcomes of surgical complications were that that occurred after the caesarian section. We divided our participants into subcategories to identify the risk factors. Results: We observed comparatively high odd ratios of the case group for all surgical complications. Within 42 days we observed 0.17% cases of bleeding, 0.22% organ damage, 0.22% of wound dehiscence, and 0.66% cases of infection were also reported. Conclusion: Our study concluded that the trend of the caesarian section is steadily increasing in past few years. However, the caesarian section has more complications when compared with vaginal deliveries. Obesity and smoking are independent risk factors for caesarian complications.